2016
DOI: 10.1558/genl.v10i3.32035
|View full text |Cite
|
Sign up to set email alerts
|

‘Off to the best start’?

Abstract: This study critically examines the multimodal discourses of baby feeding practices in contemporary health promotion in the UK. Comparing two parallel texts from the ongoing Start4life campaign (one dedicated to breastfeeding, the other to bottle/formula feeding), our multimodal critical discourse analysis identifies a series of recurring, multi-semiotic strategies through which these texts aim to promote breastfeeding as the most desirable, natural and even morally responsible method of infant nutrition. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…(Critical) studies of the discourses utilized as part of this and other campaigns have identified the linguistic mechanisms by which this individualizing, neoliberal perspective on health is realized and members of the public accordingly responsibilized for their wellbeing. For example, across a series of articles, Mulderrig (2017Mulderrig ( , 2018Mulderrig ( , 2019b investigated the use of "nudge" tactics in the Change4Life campaign, whereas Brookes and colleagues examined the use of multimodal discourses as part of emotional appeals and persuasion tactics in U.K. public health campaigns around diabetes (Brookes & Harvey, 2015), mental health (Brookes & Harvey, 2016a), baby-feeding practices (Brookes et al, 2016), and dementia (Brookes et al, 2021).…”
Section: Obesity Policy In the United Kingdom (In A Covid-19 Context)mentioning
confidence: 99%
“…(Critical) studies of the discourses utilized as part of this and other campaigns have identified the linguistic mechanisms by which this individualizing, neoliberal perspective on health is realized and members of the public accordingly responsibilized for their wellbeing. For example, across a series of articles, Mulderrig (2017Mulderrig ( , 2018Mulderrig ( , 2019b investigated the use of "nudge" tactics in the Change4Life campaign, whereas Brookes and colleagues examined the use of multimodal discourses as part of emotional appeals and persuasion tactics in U.K. public health campaigns around diabetes (Brookes & Harvey, 2015), mental health (Brookes & Harvey, 2016a), baby-feeding practices (Brookes et al, 2016), and dementia (Brookes et al, 2021).…”
Section: Obesity Policy In the United Kingdom (In A Covid-19 Context)mentioning
confidence: 99%
“…In a critical discourse analysis of two key pamphlets in the United Kingdom's National Health Service's (NHS) Start4life campaign, one focused on breastfeeding and the other on bottle‐feeding. Brookes, Harvey, and Mullaney () argued that breastfeeding ‘is elevated to a near‐mythical and inviolable status’ with bottle‐feeding constructed in a relatively negative way. These pamphlets formed part of core literature disseminated nationally to all pregnant women in the UK via health providers (Brookes et al, ) and, in the views of the authors, could result in mothers who bottle‐feed being negatively evaluated or judging themselves thus.…”
Section: Critiques Of Pro‐breastfeeding Discoursementioning
confidence: 99%
“…Brookes, Harvey, and Mullaney () argued that breastfeeding ‘is elevated to a near‐mythical and inviolable status’ with bottle‐feeding constructed in a relatively negative way. These pamphlets formed part of core literature disseminated nationally to all pregnant women in the UK via health providers (Brookes et al, ) and, in the views of the authors, could result in mothers who bottle‐feed being negatively evaluated or judging themselves thus. These findings reflect an earlier critical deconstruction of (then) current infant‐feeding material from Health Canada by Wall (); in the texts she analysed, breastfeeding was clearly linked to good motherhood, while alternative feeding methods were associated with risking the baby's health and questioning the commitment to motherhood.…”
Section: Critiques Of Pro‐breastfeeding Discoursementioning
confidence: 99%
“…52–56) and Brookes and Harvey (2016) analyzed multimodal discourses of commercialization and privatization in the websites of U.K. health care providers. Brookes, Harvey, and Mullany (2016) adopted a multimodal critical discourse approach to compare discourses of baby-feeding in public health texts about bottle and breast feeding. And, finally, in a recent study with more direct relevance to the current research, Brookes, Harvey, Chadborn, and Dening (2018) used a multimodal critical discourse approach to explore the linguistic and visual representation of dementia and people with dementia in a small sample of recent (Brookes et al, 2016) U.K. press articles.…”
Section: Introductionmentioning
confidence: 99%